Gut immune homeostasis: the immunomodulatory role of Bacillus clausii, from basic to clinical evidence. (3rd July 2022) - Wong-Chew, Rosa María; de Castro, Jo-Anne A.; Morelli, Lorenzo; Perez, Marcos; Ozen, Metehan
ABSTRACT: Introduction: The gut microbiota affects the development of the gut immune system in early life. Perturbations to microbiota structure and composition during this period can have long-term consequences on the health of the individual, through its effects on the immune system. Research in the last few decades has shown that probiotic administration can reverse these effects in strain- and environment-specific ways. Bacillus clausii ( B. clausii ) has been in use for many decades as a safe and efficacious probiotic, but its mode of action has not yet been completely elucidated. Areas covered: In this review, we discuss how the gut immune system works, the factors that affect its functioning, and the plethora of research highlighting its role in various diseases. We also discuss the known modes of action of Bacillus probiotics, and highlight the preclinical and clinical evidence that reveal how B. clausii acts to bolster gut defense. Expert opinion: We anticipate that the treatment and/or prevention of dysbiosis will be central to managing human health and disease in the future. Discovering the pathophysiology of autoimmune diseases, infections, allergies, and some cancers will aid our understanding of the key role played by microbial communities in these diseases.